HUMAN RESOURCES MANAGEMENT STRATEGY WITH INDIVIDUAL DEVELOPMENT PLAN APPROACH AND FAIR REMUNERATION TO REALIZE EMPLOYEE SATISFACTION AT PT COSMO TECHNOLOGY - Oktavina Susanti Kanday; Darmo H. Suwiryo; R. Deni Muhammad Danial (DIA: Jurnal Administrasi Publik, 2023)
The HR department is required to be active and innovative in taking part in managing company assets in the form of active human resources so that they can make a significant contribution to company profit growth. Today's human resources are seen no longer as merely an obligation but an asset that needs to be developed as a gain or capital. A new challenge for the world of HR because the implementation of the wrong HRM strategy will result in an organization not growing. There is a new paradigm, namely Human Resources has been transformed into Human Capital where the job of an HR is who has to develop strategies in the midst of global competition in the form of Talent Sortage and Talent War. So in this study the strategy used is to increase employee satisfaction through Individual development plans and fair remuneration, so that employees can create Eitengee Dageifako. this research can create a strategy that is relevant to the Individual development plan approach and fair remuneration in the company. From the research conducted, the researcher can compile an individual development plan road map and also find the X, Y, Z generations in the company who want involvement and recognition to achieve job satisfaction through a value proposition that is arranged. Meanwhile, for fair remuneration the researcher makes a job evaluation strategy using the Compasible factor with a composition of 35% Know How, 30% problem solving, and 35% responsibility, so the researchers got 7 grades in the preparation of the wage scale structure, besides that in the salary survey on the labor market the results of the calculation strategy can be said to be competitive so that the remuneration results are fair and attractive so that it is attractive to both internal and external talent.